Effect of Collagen/Ibuprofen Hydrogel in Wound Healing: An In Vivo Study - Kamyar Abbasi; Reza Eftekhar Ashtiani; Mitra Abdolahi; Maryam Hosseini; Reza Sayyad Soufdoost; Mostafa Alam; Sadaf Fani-Hanifeh (Advances in Materials Science and Engineering)
Background and Aim. Wound healing is a complicated physiological process to preserve skin integrity after injuries and includes the proliferative phase, hemostasis/inflammatory phase, and remodeling through extracellular, intercellular, and intracellular components synchronization. The study aimed to examine human placental collagen/ibuprofen’s effect on wound healing in an animal model. Materials and Methods. The cell viability test was performed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay. In this animal study, three circular excisions were made in the back of each of the 12 rats and injected with the following groups: collagen/ibuprofen, group 1; collagen, group 2; and unfilled as the control group, group 3 for two times. The healing procedures were explored via calculating wound contraction percentage after taking photographs on days 7 and 14. Also, histopathological assessments were conducted on days 7 and 14. Results. The MTT results showed no significant cytotoxicity, and macroscopic results demonstrated that the percentage of wound contraction was 85%, 79%, and 41% in the collagen/ibuprofen, collagen, and control groups on 14th day, respectively. Histopathological assessments showed that hair follicles number, fibroblasts content, and angiogenesis in the collagen/ibuprofen were remarkably more significant than collagen and control groups. Conclusion. The collagen/ibuprofen group had significant outcomes compared with collagen and the control groups in wound healing and wound contraction. Collagen/ibuprofen hydrogel can be a potential hydrogel in accelerating wound healing.